EFFECT OF AQUEOUS EXTRACT OF EUCALYPTUS LEAVES ON SOME TYPES OF GERMS THAT CAUSE OF PERIODONTAL INFLAMMATION - Shetti,Saad.H, Shetti,Saad.H; Ethar Hasan AL-shawk, Ethar Hasan AL-shawk (University of Thi-Qar Journal of agricultural research, 2024)
This study was conducted in order to identify the bacterial species that cause gingivitis, where 25 swabs were taken from the gums of gingivitis patients who were visiting specialized dental clinics in the city of Babylon between November 2022 and March 2023. To identify and isolate the bacteria that cause gingivitis, some microscopic and biochemical studies were carried out. This study revealed the existence of several types of bacteria that cause gingivitis, including: Streptococcus salivarius (2.59%), Streptococcus angiosus (2.59%) Staphyl- ococcus aureus (7.78%),Escherichia coli (5.93%),Streptococcus mutans (9.25%), Streptococcus pyogens (4.44%) Pseudomonas aeruginosa (3.33%) ,Pseudomonas monilli (1.85%) .The effect of the aqueous extract of eucalyptus leaves was also tested on the bacterial isolates above. It was found through the test that this aqueous extract of eucalyptose leaves had an inhibitory effect on the isolated bacteria, and the concentration (100 mg / ml) showed the highest inhibitory effect on the growth of bacteria. Knowing that the bacteria isolated from patients with gingivitis were sensitive to varying degrees to the antibiotics that were used in this study for the purpose of comparison, which included:ampicillin, tetracycline,Amikacin,amoxicillin,trimethoprim. The study also showed that there is a synergistic activity between the aqueous extract of eucalyptus leaves with the antibiotic Amkasin for the growth of bacteria. The study concluded that the extracts of some medicinal plants should be used as an alternative to antibiotics.